A fuzzy LSP regulator for preemption control in a DiffServ-aware MPLS internet - Din N.M.; Abidin H.Z.; Rahman S.F.A.; Fisal N. (2023)
This paper describes a proposal for a fuzzy logic LSP regulator for preemption control in a DiffServ-aware MPLS Internet network based on the Russian Doll bandwidth allocation scheme. The fuzzy logic regulator regulates the incoming traffic based on class by either rerouting or resizing existing less prioritized traffic or rejecting the admission request. Three DiffServ traffic class types were used in the DiffServ-aware MPLS network under study, i.e. premium, assured and best effort traffic. The fuzzy logic regulator uses the premium traffic utilization value, the assured and best effort traffic amount of borrowed bandwidth information as inputs and the preemption decision as output. A simulation study was performed for the fuzzy logic regulator using ns-2. A comparative analysis was conducted with preemption, no preemption and with fuzzy logic regulator preemption. The results show that the fuzzy logic pre-emption scheme gave better performance in terms of connection blocking probability and throughput. 2005 IEEE.